Application of Cooperative Learning and Flipped Classrooms in University Basketball Courses in China - Yun-Jie, Li; Wan Norizan, Wan Hashim; Ross Azura, Zahit (Bio-Byword Scientific Publishing Pty. Ltd., 2024)
This study investigates the application of the teaching model combining cooperative learning and flipped classrooms in university basketball courses in China. By analyzing the advantages and disadvantages of the traditional basketball teaching model and students’ satisfaction with the course, the necessity of implementing cooperative learning and flipped classrooms is proposed. The study planned in detail the implementation strategies before class, in the classroom, and after class, and compared them with the control group through an experimental design. The experimental results showed that the new teaching mode demonstrated significant advantages in terms of learning outcomes, student satisfaction, and teacher evaluation. This study provides a valuable reference for the future reform of the physical education curriculum.